Comparison of Asthma Gymnastic and Static Ergocycle Exercise in Improving VO2max and Quality of Life in Adult Asthmatic Patient - Tina Susilawati; Tri Damiati Pandji; Arto Yuwono Soeroto (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Objective: To compare two aerobic exercise training program, asthma gymnastic and static ergocycleexercise, in improving VO2max and QoL based on St. George’s Respiratory Questionaire (SGRQ)for partially-controlled asthmatic patients.Methods: This study analysed 36 of partially-controlled asthmatic adult patients (aged 21-50 yearsold) which were divided into two groups, asthma gymnastic (A, n=18) and ergocycle exercise (B,n=18) each for 3x/week for 6 weeks. Before and after treatment, VO2max was measured usingAstrand ergocycle method and QoL using SGRQ.Results: Significant increase of mean VO2max in both groups (A 3.78 ml/kg/minute vs B 7.13 ml/kg/minute in group B; p 0.00). Significant improvements were also found in all component of SGRQ(p=0.00) in both groups, with higher total score found in group B (A 271.11 vs B 384.86, p=0.00).Conclusion: Static ergocycle exercise increased the level of VO2 max and QoL in partially-controlledasthmatic adult patients better than asthma gymnastic.Keywords: Asthma gymnastic, static ergocycle exercise, partially-controlled asthma, quality of life, VO2max